Pulsus Group, the Canadian Association of Gastroenterology and CDDW (Canadian Journal of Gastroenterology)
At the recent Canadian Digestive Diseases Week in Banff, Alberta, the third annual Dr ABR Thomson - Dr CN Williams Award was presented to Dr Krikor Kichian. This Award was initiated in 2002 by Pulsus Group in honour of Drs Alan Thomson and Noel Williams, the founding Co- Editors-in-Chief of The Canadian Journal of Gastroenterology, who served from 1987 to 2000. Robert Kalina, publisher of The Canadian Journal of Gastroenterology, invited Dr Williams to present the award to Dr Kichian.